Cytoprotective Effect of Morchella esculenta Protein Hydrolysate and Its Derivative Against H2O2-Induced Oxidative Stress - Qiang Zhang; Caie Wu; Yujun Sun; Tingting Li; Gongjian Fan (Polish Journal of Food and Nutrition Sciences, 2019)
Morchella protein hydrolysate (MPH) and its glycosylated derivative (G-MPH) may possess the potential as natural antioxidants. However, knowledge about the protective effects of MPH and G-MPH on cellular oxidative damage is limited. This study evaluated whether MPH and G-MPH protected Caco-2 cells from H2O2-induced oxidative injury and explored the potential mechanisms of protection. The results showed that, under H2O2 stress, both MPH and G-MPH significantly increased cell viability, suppressed intracellular ROS and MDA production, increased cellular antioxidant capacity, and activated Nrf2 signaling pathway. More importantly, MPH and G-MPH significantly inhibited the H2O2-induced apoptosis via restoring the loss of mitochondrial membrane potential and regulating the protein expressions of Bax, Bcl-2, and caspase-3. These data indicate that MPH and G-MPH can protect Caco-2 cells against oxidative injury by improving cellular antioxidant responses and inhibiting apoptosis. Therefore, MPH and G-MPH can have a broad application potential as promising ingredients of nutraceutical products or functional foods.